Experience of patients and carers with traditional healing and psychiatric services, and the outcome of psychosis for patients who attend traditional services in Sudan / Ehab Ali Sorketti Koriana - Koriana, Ehab Ali Sorketti (2013)
The use of traditional healers is common worldwide, especially in developing countries. Few studies, though, have focused on the use of traditional healers by people with mental disorders. This study made an attempt to understand the practice of traditional healers in relation to mental health and psychiatric services in Sudan. The study was framed to understand: (a) the socio-demographic characteristics of people with mental disorders who seek treatment in the traditional healer centres in central Sudan; (b) the clinical presentations, diagnoses and outcomes of people with psychotic disorders attending traditional healers, as well as the healing methods and interventions used; (c) the traditional healers’ profiles – their knowledge, belief, attitudes and practice in relation to people with mental disorders. Applying both qualitative and quantitative methods, the research was conducted in four phases, as follows. In phase 1 we interviewed the traditional healers to study their profile, their socio-demographic characteristics and their opinions on medical treatment and the possibilities for collaboration with mental health professionals. In phase 2 we carried out focus group discussions with the relatives accompanying patients with mental disorders at traditional healer centres, to explore their concepts and beliefs about mental illness, traditional healing and psychiatric treatment. In phase 3 we interviewed the patients with mental disorders receiving treatment at the traditional healer centres in Sudan to assess their socio-demographic characteristics and the type of mental disorders they have. In phase 4 we followed up the group of psychotic patients (only schizophrenics) to see the outcome of the traditional healer’s management. Ten traditional healer centres in central Sudan were randomly selected. They had a total of 405 inpatients with mental disorders undergoing treatment. Twenty-eight of 30 traditional healers at these centres agreed to participate in the study. The measures and instruments consisted of structured questionnaires, the Mini International Neuropsychiatric Interview (MINI) to elicit diagnoses, and the Positive and Negative Syndrome Scale (PANSS), used to assess the psychotic group of patients on admission and discharge from traditional healer centres. Ethical approval was obtained before the start of the study and informed consent was obtained from all the participants. A total of 405 patients were interviewed; 309 (76.3%) were male and 96 (23.7%) were female. Their mean age was 31.48 years; 69.4% (281) were from central Sudan; 64.4% (261) were single; 34.1% (138) had never been to school, 39.3% (159) had studied in primary school, and 19.5% (79) studied until secondary school level; 46.9% (190) were jobless. The mean duration of stay in the traditional healer centre was 5 months. The mean duration of untreated illness was about 14 months. The diagnostic breakdown was as follows: 15.8% (64) had major depressive disorder, 27.4% (111) had a manic episode, 34.6% (140) had a psychotic disorder, and 5.9% (24) had generalized anxiety disorder. Interventions at the centres included restriction of food in 86.9% of cases (352), chaining the patient in 69.9% (283), isolation of the patient in 33.3% (135), and not allowing visitors in 15.8%. Psychiatric medications were stopped by the healers for 18% of the patients. Recitation of the holy book was used as a method of treatment for all patients. Bakhra was used in 99.3% of cases and Mehaya in 93.1%. To study the outcome of the traditional healers’ intervention, 129 patients with psychotic disorders (schizophrenia) were followed up from admission until discharge from the traditional healer centre. The mean overall PANSS score was 118.36 on admission and 69.36 on discharge, a 49% reduction (p=0.0001). A total of 28 traditional healers were interviewed to assess their concept, attitude and practice towards people with mental disorders. Fifteen (54%) of the healers believed that psychiatric medication was useful for treating mental illness, and they believed that combining traditional treatment and psychiatric medication could be useful. Belief in the value of psychiatric medication and modern psychiatric management was related to the educational level of the traditional healer: the more years of formal education the healer had received, the stronger was the belief in modern methods of management, and the use of psychiatric medication for treating people with mental illness (p = 0.05). A total of 89% (25) of the traditional healers were ready to collaborate with psychiatrists and mental health services. It is vital to establish channels of collaboration and common understandings between traditional healers and mental health professionals in Sudan, where a majority of people with mental illness consult traditional healers first. Collaboration could help in the early detection and early management of mental disorders, with the prospect of better outcomes. Collaboration can also help to end harmful methods of practice by the traditional healers. The traditional healer centres can be used as bases for community rehabilitation facilities for people with mental illness. Moreover, improving the education level of traditional healers might enable them to have a better understanding of mental illness and of the benefits of modern psychiatric treatment.